The Meaning of the Recitation (Arabic: قرائت) of the Quran at the Last Verse of Sūrah al-Muzzammil and Its Islamic Law Verdict (Hukm Shar'ī) - Hamid Vahidian Ardakan; Hasan Naqizadeh; Muhammad hasan Rostami (آموزه‌های قرآنی)
At the last verse of sūrah al-Muzzammil (Arabic: سورة المزّمّل) has been commanded to the recitation (Arabic: قرائت) of the Quran. There is no consensus about the meaning of “recitation”. Some believe that the meaning of the recitation of the holy Quran in this verse is exclusively “recitation” (Arabic: قرائت) and it does not mean the recitation that is of the obligatory acts of prayer which are not invalidate the prayer if they are left or added unintentionally. Some think that the meaning of this “recitation” is exclusively the recitation in the prayer including the obligatory or recommended prayers. The great scholars such as Sayyed Murtaza, Allameh Helli, Muhaqiq Karaki and ayatollah Khui have acquired from this verse that the obligation of the recitation in the daily obligatory prayers and some others have believed that its meaning is a recommended matter for the night prayer. With accurate look to the meaning of standing in the night (qiyaam al-layl, Arabic: قیام اللیل) and its uses in the preceding texts and carefulness it is cleared the accuracy in speech situation, the linguistic sense (siaq) and the structure of the verse and surah that the first three sayings (opinions) because of being contrary to the appearance of the verse and the structure of surah and the opposition to speech situation and hadiths the first three sayings (opinions) are not accepted. With applying proofs such as accordance with the rhetorical principles, conformity with the linguistic sense (siaq) of the verse and surah, speech situation and hadiths the fourth saying (opinion) is proved. It reveals that the direct command in this statement contrary to the imperative form indicates a recommended matter. The semantics of the composition of «قیام اللیل» (verbal meaning: standing in the night) and utilizing it in this debate and also argument to speech situation, the surah structure, the rhetorical principle “epanastrophe” are of the paper innovations.